Implications of Trauma-Sensitive Practices at the Middle Level - Lauren Dotson Davis (Middle Grades Review, 2019)
This essay provides a broad overview of adverse childhood experiences and their impact on the middle level learner. Through a literature review, the author finds points of intersection between current research on traumatized students, best practices for classroom and school-wide procedures, and tenets of the middle level philosophy.
Keywords: Trauma; Middle Level; Classroom Management Strategies; School Discipline Policies; Adverse Childhood Experiences